The Evidence of Microfinance as a Tool in Poverty Alleviation in Malaysia A Survey - Ahmad Nazrie, Mohd Nor; Senthil Kumar, T. (IFERP, 2021)
Poverty issues still prevalent in Malaysia and microfinance is one of the best available tools to overcome that situation because it provides loans with fewer regulations. Response from 330 respondents were acquired to bolster this fact and this paper projects strong evidences on the effectiveness of microfinance and its potential to eradicate poverty in Malaysia using Partial Least Square-Structural Equation- Modelling (PLS-SEM). The results of the study show that there is a significant relationship between loan features and training development on social wellbeing, employee generation, household income and micro enterprise performance.